Colloidal quantum dot lasing for lighting and displays - Gao, Yuan (2016)
Semiconductor light-emitting diodes (LEDs) enable artificial lighting with an unprecedented level of efficiency. However, “efficiency droop” occurs in LEDs under high power injection density, practically limiting the feasible efficiency levels at high output powers. To address this problem, the concept of laser lighting has been proposed. Also, the current liquid crystal displays (LCDs) suffer the problems of low energy efficiency and small colour gamut, which can be addressed by employing the polarized white backlighting and saturated primary colours. Lasers with colloidal quantum dots (CQDs) as a gain medium can provide solutions to these limitations of current lighting and display technologies. Thus, the target of my Ph.D. thesis work is to develop and demonstrate low threshold colloidal quantum dot lasing with high linear polarization. In Chapter 2 of this thesis, unique properties of CQDs, including size dependent bandgap and discrete energy levels, which result from quantum confinement effect, are discussed. Here by adjusting the size, structure and chemical composition, CQDs that emit at various targeted wavelengths were synthesized. The resulting optical and structural characterizations are also presented. In Chapter 3, a brief review of the optical gain from CQDs is given, and the means that can be adopted to abate Auger recombination are discussed. In experimental part, CQD lasing of red, green, and blue CQDs was demonstrated. Moreover, a FRET-assisted indirect pumping scheme for CQD green lasing with standard pumping source was developed. In Chapter 4 and Chapter 5, highly polarized lasing from CQDs was demonstrated by utilization of the optical cavity effect and adoption of the polarized gain medium, respectively. The CQD DFB laser with mechanically flexible substrate was shown and analysed in Chapter 4. However, for a cylindrical optical cavity of a large diameter, which has low selectivity of TE and TM mode, the polarized gain medium that was fabricated by aligned nanorods was employed for realizing highly polarized Whispering Gallery mode lasing. These results indicate that highly polarized CQD lasing can find important uses in future lighting and displays.